2018
DOI: 10.1063/1.5027270
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of flexible polymer chains on a surface: Effects of different solvent conditions

Abstract: Polymer chains undergoing a continuous adsorption-desorption transition are studied through extensive computer simulations. A three-dimensional self-avoiding walk lattice model of a polymer chain grafted onto a surface has been treated for different solvent conditions. We have used an advanced contact-density chain-growth algorithm, in which the density of contacts can be directly obtained. From this quantity, the order parameter and its fourth-order Binder cumulant are computed, as well as the corresponding c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…It is important to notice that the estimate of φ (s) is highly dependent on the precise location of the adsorption point, but no such argument can be made for the method of estimating 1/δ (s) . However, it is also important to highlight that the presence of strong finitesize corrections seriously affects exponent estimates for the ordinary surface transition, having recently led to claims of non-universality in the case of self-avoiding walks [10,16]. We also find evidence for strong finite-size corrections at the special point.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…It is important to notice that the estimate of φ (s) is highly dependent on the precise location of the adsorption point, but no such argument can be made for the method of estimating 1/δ (s) . However, it is also important to highlight that the presence of strong finitesize corrections seriously affects exponent estimates for the ordinary surface transition, having recently led to claims of non-universality in the case of self-avoiding walks [10,16]. We also find evidence for strong finite-size corrections at the special point.…”
Section: Resultsmentioning
confidence: 59%
“…These findings are relevant with regards to the recently claimed non-universality of the adsorption transition for polymers in the presence of bulk interactions [10,16]. This was based on simulations of relatively short selfavoiding walks of lengths up to 503 steps on the simple cubic lattice.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…[4] The behavior of multiblock for ring chains at least at good solvent conditions; the crossover exponent was found the same for both architectures. [71] The critical behavior near the transition from weak to strong adsorption was recently described and discussed, [62,72] thus in this work we focused on the changes in the structure of adsorbed chains governed by the competition of intrachain and surfacechain interactions. The influence of temperature, chain length, sequence of beads, and strength of adsorption on the structure of cyclic polymer chains was studied.…”
Section: Introductionmentioning
confidence: 98%
“…Numerical simulation is thus a useful tool in this field and can be applied to other questions. For the effect of the bulk interaction on polymer adsorption, recent work by Plascak et al [18,19] has suggested that altering the strength of the bulk interactions with respect to the surface interactions has a significant effect on φ and the critical temperature T ads . For the case where the bulk interaction is made increasingly repulsive the critical temperature decreases slightly from the noninteracting case.…”
Section: Introductionmentioning
confidence: 99%